IMPLICATIONS OF APPLICATION OF LAW NUMBER 11 OF 2020 CONCERNING CREATION OF WORK ON THE IMPLEMENTATION OF HALAL PRODUCT ASSURANCE - Farid Wajdi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This study analyzed the implications of the enactment of Law Number 11 of 2020 concerning Job Creation on the Implementation of Halal Product Guarantee. This is normative juridical research. The data gathered through secondary data and the research specification wss descriptive-analytical. The data analysis was done qualitatively. This paper concludes that the enactment of Law Number 11 of 2020 concerning Job Creation has brought amendments to 22 articles and the addition of 2 new articles in Law Number 33 of 2014 concerning Halal Product Guarantee. There have been a number of significant changes in the implementation of the Halal Product Guarantee, including the matter of convenience for micro and small businesses, cutting the length of time for the application and the halal certification process, and changing a number of sanctions related to the regulation of halal product guarantees. The implications of this change are clearly visible in the halal certification business process, the cooperation between Halal Product Guarantee Agency (HPGA), the Halal Inspection Agency (HIA) and halal auditors, halal supervisors, community participation, halal certificates, halal labels, self-declare, and administrative sanctions.